Profile of Biology Teachers' Ability in Microbiology Practicum Trials Based on Local Materials During the Covid-19 Pandemic in Senior High School - Kusnadi Kusnadi; Yanti Hamdiyati; Peristiwati Peristiwati; Any Fitriani; Purnamaulida Pratiwi; Fitri Husni; Aditia Pratama (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to determine the profile of the ability of senior high school biology teachers in designing and testing local material-based bacteria and fungi cultivating practices during the Covid-19 pandemic. The method used in this study is a descriptive method with a qualitative approach. The participants in this study were 33 senior high school biology teachers at West Java province, Bandung. The data collection technique used the lesson plan assessment rubric, student worksheet, and practicum trial reports, besides that used both teacher profile and activities and obstacles questionnaires during the training. The research data analysis technique used data triangulation, data presentation, and conclusions. The data validity test includes data testing, data reliability testing, external validity/generalization. The results show that the profile of Senior High School biology teachers regarding teaching experience, as many as 63% of teachers had more than 10 years of teaching experience. The achievement of eligibility obtained a score of 85% (good category). These criteria include content, presentation, language, graphics, ease of usage, suitability of appearance, and usability of student worksheet features. The results of the questionnaire show that 91% of participants thought that the design and practical trial activities are very useful, 83% of participants thought that the material that had been delivered could be applied in schools. So that biology teachers can innovate further by using local materials to carry out practicum activities.